Pulmonary Limitations in Heart Failure - Cundrle, Ivan; Olson, Lyle J; Johnson, Bruce D (Clinics in chest medicine, 2019)
The heart and lungs are intimately linked. Hence, impaired function of one organ may lead to changes in the other. Accordingly, heart failure is associated with airway obstruction, loss of lung volume, impaired gas exchange, and abnormal ventilatory control. Cardiopulmonary exercise testing is an excellent tool for evaluation of gas exchange and ventilatory control. Indeed, many parameters routinely measured during cardiopulmonary exercise testing, including the level of minute ventilation per unit of carbon dioxide production and the presence of exercise oscillatory ventilation, have been found to be strongly associated with prognosis in patients with heart failure.
Keywords: zátěžový test; Female; Lung; Cardiopulmonary exercise testing; Humans; ženské pohlaví; mužské pohlaví; Heart Failure; lidé; srdeční selhání; Male; Heart failure; Exercise Test; Ventilatory efficiency; plíce; Pulmonary Gas Exchange; výměna plynů v plicích